Rainwater Harvesting of Hauran Valley, West of Iraq - A. Alhadithi , Abdulkhaleq; A. Alaraji, Ammar (Iraqi Journal of Science, 2023)
The aim of this paper is to study the rainwater harvesting of Hauran valley in Iraqi Western Desert by using remote sensing techniques. Drainage patterns of secondary valleys are drawn. Digital Elevation Model (DEM) is applied to determine the typical locations of small dams or barriers of concrete or soil. Small lakes along Hauran valley will do to increase urban activities and can be useful for agriculture, irrigation and development of artificial forests to decrease the desertification phenomenon.